Identification and characterization of acid and alkaline phosphatases and protein phosphatases in L. catesbeianus tail during metamorphosis - Gonçalves, Adriano Marques [UNESP]; Santana, Caroline Carla [UNESP]; Santos, Luiz Flávio José Dos [UNESP]; Colosio, Rafael Rodrigues [UNESP]; Balbuena, Tiago Santana [UNESP]; Pizauro, João Martins [UNESP] (Springer Nature, 2021)
Amphibian metamorphosis is a tightly regulated transformation involving the participation of hormones and other biomolecules in cell death and tail absorption. Among the regulators, phosphate is essential for various processes, such as cell death and survival and enzyme activity regulation. Therefore, identification and characterization of phosphatases in L. catesbeianus tail may contribute to understand the events involved in cell death and nutrient release during metamorphosis. Differential centrifugation was used to separate soluble proteins from membrane proteins and analyzed by phosphomonohydrolases, serine/threonine protein phosphatase 2A (PP2A), and protein tyrosine phosphatase (PTP) assays. Mitochondrial fractioning was used to evaluate PP2A and alkaline phosphatase activities. Tandem mass spectrometry (MS/MS) analysis was performed using the crude extract. Phosphomonohydrolase activity was assayed by p-nitrophenylphosphate (pNPP) hydrolysis, whereas PP2A and PTP were assayed by peptides phosphorylated in threonine and tyrosine, respectively; inhibitor-2 was used to identify the serine/threonine protein phosphatase type 1 (PP1). The enzymatic activities and kinetic parameters of pNPP hydrolysis revealed three distinct phosphomonohydrolases. MS/MS analysis of the crude extract revealed three protein phosphatases, viz., PP2A, PP1, and a PTP, which was confirmed by in vitro assays. The results may relate PP2A activity to membrane-bound alkaline phosphatase, PTP activity to soluble acid phosphatase, and PP1 activity to membrane acid phosphatase, although more detailed studies are needed to confirm this hypothesis. We propose a model providing information on the role of PP1 and PP2A in the signaling events leading to cell death and the role of these enzymes in anuran tail absorption during metamorphosis.
Keywords: Anura; Cell death; Metamorphosis; Mitochondria; Phosphatases; PP1; PP2A